1991
DOI: 10.1128/iai.59.11.3869-3875.1991
|View full text |Cite
|
Sign up to set email alerts
|

Plasmid and chromosomal elements involved in the pathogenesis of attaching and effacing Escherichia coli

Abstract: Attaching and effacing (A/E) intestinal lesions are produced by enteropathogenic Escherichia coli (EPEC), enterohemorrhagic E. coli (EHEC), and RDEC-1, a pathogen of weanling rabbits. We recently identified a chromosomal locus (eae [E. coli A/E]) which is required for A/E activity in a wild-type EPEC strain. Sequences homologous to those of an eae gene probe were detected in EPEC, RDEC-1, and EHEC isolates. We report here that the eae gene is chromosomally encoded in all EPEC and EHEC strains tested and in RDE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
58
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(58 citation statements)
references
References 54 publications
0
58
0
Order By: Relevance
“…(eae) mechanisms, the maintenance of 'large-sized plasmids', and the production of enterohemolysins [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…(eae) mechanisms, the maintenance of 'large-sized plasmids', and the production of enterohemolysins [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Among the different pathogroups in E. coli, one common principle called attaching and effacing has been detected in EPEC and EHEC (12,24). E. coli isolates which produce the AE lesion are termed as attaching and effacing E. coil (AEEC) (9,22). Knutton et al (12,13) developed a highly specific method, the FAS test, for identifying E .…”
Section: Fas Assaymentioning
confidence: 99%
“…coli which demonstrate AE activity. The cloning and sequencing of the eaeA gene, which mediates the AE lesion, made it possible to develop a DNA probe for (9,10), and to evaluate its association with diarrhea in epidemiological studies (7,23). Schmidt et al (21) reported that prevalence of the eaeA gene in EPEC belonging to classical serotypes and EHEC were 32.…”
Section: Fas Assaymentioning
confidence: 99%
See 2 more Smart Citations